Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Semen Tiga Roda di Kabupaten Karawang - Ramgendi; Siregar, Salim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out, analyze and explain how big the partial and simultaneous influence of Product Quality and Price is on the Purchase Decision of Tiga Roda Cement in Karawang Regency. The method used in this research is descriptive and verification research methods. This type of research is quantitative research. The population in this study focused on consumers of Tiga Roda cement products in the Karawang Regency area. The number of samples from this research was 225 people from consumers of Semen Tiga Roda using a purposive sampling technique. The analytical tool used in this research uses multiple linear regression analysis. The research results show that there is a partial or simultaneous influence between product quality and price on purchasing decisions for Tiga Roda Cement in Karawang Regency. The magnitude of the influence of product quality and price on purchasing decisions is 83.6%. Meanwhile, the influence of other variables outside the model is 16.4%.